Low-Energy Traumatic Obturator Hip Dislocation with Ipsilateral Femoral Shaft Fracture in a Patient with Omolateral Knee Arthroplasty - G. Gazzotti; L. Patrizio; S. Dall’Aglio; E. Sabetta (Case Reports in Orthopedics)
Ipsilateral obturator hip dislocation and femoral shaft fracture are rare. We report such a case in an older woman after a low-energy injury. She had a knee prostheses in the same limb. The patient was treated by open manipulative reduction of the luxation without opening joint and open reduction and internal fixation of the femur with angular stability plate and screws. We could not find a similar case in the literature. An early diagnosis of the dislocation is crucial in order to obtain good results. Great awareness and radiologic examination are fundamental to achieve precocious diagnosis of both these rare combined injuries, as treatment in these cases is considered an emergency. The first step was an attempt to reduce the dislocation by closed means but it failed. Then we performed a short approach at the trochanteric region and used Lambotte forceps to manoeuvre the proximal femur without opening the joint achieving reduction. Thereafter the femoral shaft fracture underwent open reduction and internal fixation with an angular stable plate. After a 2-year follow-up the outcome was very good.